Influence of bulky yet flexible N-heterocyclic carbene ligands in gold catalysis - Collado, Alba; Patrick, Scott R.; Gasperini, Danila; Meiries, Sebastien; Nolan, Steven P. (Beilstein Journal of Organic Chemistry, 2015)
Three new Au(I) complexes of the formula [Au(NHC)(NTf2)] (NHC = N-heterocyclic carbene) bearing bulky and flexible ligands have been synthesised. The ligands studied are IPent, IHept and INon which belong to the ‘ITent’ (‘Tent’ for ‘tentacular’) family of NHC derivatives. The effect of these ligands in gold-promoted transformations has been investigated.
Keywords: catalysis; flexible and bulky ligands; gold; ligand design; N-heterocyclic carbenes

Advances in Organometallic Chemistry and Catalysis - Gagosz, F. (Organogold Catalysis: Homogeneous Gold-Catalyzed Transformations for a Golden Jubilee, 2013)

Organometallics in Synthesis - Krause, N. (Organogold Chemistry, 2013)

(untitled) - Nolan, S. P. (Acc. Chem. Res., 2011)

(untitled) - Rudolph, M.; Hashmi, A. S. K. (Chem. Commun., 2011)

(untitled) - Li, Z.; Brouwer, C.; He, C. (Chem. Rev., 2008)

(untitled) - Hashmi, A. S. K. (Chem. Rev., 2007)

(untitled) - Hashmi, A. S. K.; Hutchings, G. J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Hashmi, A. S. K.; Schwarz, L.; Choi, J.-H.; Frost, T. M. (Angew. Chem., Int. Ed., 2000)

(untitled) - Hashmi, A. S. K.; Frost, T. M.; Bats, J. W. (J. Am. Chem. Soc., 2000)

(untitled) - Riedel, D.; Wurm, T.; Graf, K.; Rudolph, M.; Rominger, F.; Hashmi, A. S. K. (Adv. Synth. Catal., 2015)

(untitled) - Hashmi, A. S. K.; Lothschütz, C.; Graf, K.; Häffner, T.; Schuster, A.; Rominger, F. (Adv. Synth. Catal., 2011)

(untitled) - Hashmi, A. S. K.; Lothschütz, C.; Böhling, C.; Hengst, T.; Hubbert, C.; Rominger, F. (Adv. Synth. Catal., 2010)

N-Heterocyclic Carbenes: Effective Tools for Organometallic Synthesis - Nolan, S. P. (Wiley-VCH Verlag GmbH & Co. KGaA, 2014)

(untitled) - Hopkinson, M. N.; Richter, C.; Schedler, M.; Glorius, F. (Nature, 2014)

(untitled) - Nelson, D. J.; Nolan, S. P. (Chem. Soc. Rev., 2013)

N-Heterocyclic Carbenes: From Laboratory Curiosities to Efficient Synthetic Tools - Diez-Gonzalez, S. (The Royal Society of Chemistry, 2011)

(untitled) - Clavier, H.; Nolan, S. P. (Chem. Commun., 2010)

(untitled) - Dröge, T.; Glorius, F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Díez-González, S.; Marion, N.; Nolan, S. P. (Chem. Rev., 2009)

N-Heterocyclic Carbenes in Transition Metal Catalysis - Glorius, F. (Springer, 2007)

(untitled) - Meiries, S.; Le Duc, G.; Chartoire, A.; Collado, A.; Speck, K.; Arachchige, K. S. A.; Slawin, A. M. Z.; Nolan, S. P. (Chem. – Eur. J., 2013)

(untitled) - Jafarpour, L.; Stevens, E. D.; Nolan, S. P. (J. Organomet. Chem., 2000)

(untitled) - Würtz, S.; Lohre, C.; Fröhlich, R.; Bergander, K.; Glorius, F. (J. Am. Chem. Soc., 2009)

(untitled) - Würtz, S.; Glorius, F. (Acc. Chem. Res., 2008)

(untitled) - Altenhoff, G.; Goddard, R.; Lehmann, C. W.; Glorius, F. (J. Am. Chem. Soc., 2004)

(untitled) - Altenhoff, G.; Goddard, R.; Lehmann, C. W.; Glorius, F. (Angew. Chem., Int. Ed., 2003)

(untitled) - Soleilhavoup, M.; Bertrand, G. (Acc. Chem. Res., 2015)

(untitled) - Chartoire, A.; Lesieur, M.; Falivene, L.; Slawin, A. M. Z.; Cavallo, L.; Cazin, C. S. J.; Nolan, S. P. (Chem. – Eur. J., 2012)

(untitled) - Chartoire, A.; Frogneux, X.; Nolan, S. P. (Adv. Synth. Catal., 2012)

(untitled) - Berthon-Gelloz, G.; Siegler, M. A.; Spek, A. L.; Tinant, B.; Reek, J. N. H.; Markó, I. E. (Dalton Trans., 2010)

(untitled) - Lavallo, V.; Canac, Y.; Präsang, C.; Donnadieu, B.; Bertrand, G. (Angew. Chem., Int. Ed., 2005)

(untitled) - Groombridge, B. J.; Goldup, S. M.; Larrosa, I. (Chem. Commun., 2015)

(untitled) - Sharif, S.; Rucker, R. P.; Chandrasoma, N.; Mitchell, D.; Rodriguez, M. J.; Froese, R. D. J.; Organ, M. G. (Angew. Chem., Int. Ed., 2015)

(untitled) - Marelli, E.; Corpet, M.; Davies, S. R.; Nolan, S. P. (Chem. – Eur. J., 2014)

(untitled) - Pompeo, M.; Farmer, J. L.; Froese, R. D. J.; Organ, M. G. (Angew. Chem., Int. Ed., 2014)

(untitled) - Suzuki, Y.; Fukui, N.; Murakami, K.; Yorimitsu, H.; Osuka, A. (Asian J. Org. Chem., 2013)

(untitled) - Hoi, K. H.; Coggan, J. A.; Organ, M. G. (Chem. – Eur. J., 2013)

(untitled) - Le Duc, G.; Meiries, S.; Nolan, S. P. (Organometallics, 2013)

(untitled) - Valente, C.; Çalimsiz, S.; Hoi, K. H.; Mallik, D.; Sayah, M.; Organ, M. G. (Angew. Chem., Int. Ed., 2012)
and references therein

(untitled) - Organ, M. G.; Çalimsiz, S.; Sayah, M.; Hoi, K. H.; Lough, A. J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Çalimsiz, S.; Sayah, M.; Mallik, D.; Organ, M. G. (Angew. Chem., Int. Ed., 2010)

(untitled) - Collado, A.; Balogh, J.; Meiries, S.; Slawin, A. M. Z.; Falivene, L.; Cavallo, L.; Nolan, S. P. (Organometallics, 2013)

(untitled) - Poater, A.; Cosenza, B.; Correa, A.; Giudice, S.; Ragone, F.; Scarano, V.; Cavallo, L. (Eur. J. Inorg. Chem., 2009)

(untitled) - Patrick, S. R.; Collado, A.; Meiries, S.; Slawin, A. M. Z.; Nolan, S. P. (J. Organomet. Chem., 2015)

(untitled) - Ricard, L.; Gagosz, F. (Organometallics, 2007)

(untitled) - Mézailles, N.; Ricard, L.; Gagosz, F. (Org. Lett., 2005)

(untitled) - Gaillard, S.; Slawin, A. M. Z.; Nolan, S. P. (Chem. Commun., 2010)

(untitled) - Gasperini, D.; Collado, A.; Goméz-Suárez, A.; Cordes, D. B.; Slawin, A. M. Z.; Nolan, S. P. (Chem. – Eur. J., 2015)

(untitled) - Gómez-Suárez, A.; Ramón, R. S.; Songis, O.; Slawin, A. M. Z.; Cazin, C. S. J.; Nolan, S. P. (Organometallics, 2011)

(untitled) - Wang, Y.; Wang, Z.; Li, Y.; Wu, G.; Cao, Z.; Zhang, L. (Nat. Commun., 2014)

(untitled) - Gómez-Suárez, A.; Oonishi, Y.; Meiries, S.; Nolan, S. P. (Organometallics, 2013)

(untitled) - Nun, P.; Ramón, R. S.; Gaillard, S.; Nolan, S. P. (J. Organomet. Chem., 2011)

(untitled) - Czégéni, C. E.; Papp, G.; Kathó, Á.; Joó, F. (J. Mol. Catal. A: Chem., 2011)

(untitled) - Leyva, A.; Corma, A. (J. Org. Chem., 2009)

(untitled) - Marion, N.; Ramón, R. S.; Nolan, S. P. (J. Am. Chem. Soc., 2008)

(untitled) - Sanz, S.; Jones, L. A.; Mohr, F.; Laguna, M. (Organometallics, 2007)

(untitled) - Mizushima, E.; Sato, K.; Hayashi, T.; Tanaka, M. (Angew. Chem., Int. Ed., 2002)

(untitled) - Ramón, R. S.; Gaillard, S.; Poater, A.; Cavallo, L.; Slawin, A. M. Z.; Nolan, S. P. (Chem. – Eur. J., 2011)

(untitled) - Ramón, R. S.; Marion, N.; Nolan, S. P. (Chem. – Eur. J., 2009)

(untitled) - Gómez-Suárez, A.; Gasperini, D.; Vummaleti, S. V. C.; Poater, A.; Cavallo, L.; Nolan, S. P. (ACS Catal., 2014)

(untitled) - Ketcham, J. M.; Biannic, B.; Aponick, A. (Chem. Commun., 2013)